As exigências de performatividade e seus impactos na identidade dos diretores escolares: municipio de Contagem-MG - Marcos Welington de Lima (2011)
This dissertation is aimed to analyze the impacts of schools external evaluations to the identity of the principals of elementary schools in Contagem / MG. The identity was examined based on the performativity requirements settled in schools external evaluations as well as in the competition created by the principal election. This paper has attempted to answer the question: How to create an identity structure of the principals before the demands of performativity? Or even, How is the subjectivity of the principals before external evaluations? It is a study that is located in the micro-political area, in other words, the space is the school unit, where they embody the educational activities that are part of the legislation and policies of the county. Despite the fact that the theoretical expectation involves some concepts already worked on the organizations sociology and also in Management Theories, the analytical approach that has been the most important so far was the one about the speeches of the actors directly involved. Therefore, we led 20 interviews from a previous established schedule. The survey was led with the Department of Education and Culture of Contagem and has considered the following information: number of schools, number of elected principals, number of students, number of employees, the rules of election and terms of office, the electoral college. In each and every one of the 69 schools was gathered information about: age of the officer or principal, principals academic background, length of service in public schools. Then semi-structured interviews were conducted with a principal and two teachers from each regional educational group, with the Education Secretary and the core member of one regional group. In the interviews, themes such as community participation, the operation of the Board, the principal's relationship with the Education Department and the impacts of the external evaluations